Penilaian Kinerja Dinas PUPR Terhadap Kondisi Jalan di Kabupaten Bangkalan Tahun 2024 - Nur Alfi Laili; Mudji Kuswinarno (BADAN PENERBIT STIEPARI PRESS, 2024)
This research analyzes the performance of the Bangkalan Regency PUPR Service in handling road conditions in 2024. Using descriptive qualitative methods, this study found a significant decline in road quality from 2021-2023, with roads in good condition decreasing and heavily damaged increasing. The PUPR Department is facing major challenges due to budget cuts from 60 billion to 20 billion for preparations for the 2024 regional elections, causing a reduction in road repair plans. The research recommends priority improvement strategies, exploration of alternative funding, increased efficiency, and regular evaluation of the PUPR Service's performance to overcome road infrastructure problems that impact mobility and the community's economy.